2H‑Azirine-Based Reagents for Chemoselective Bioconjugation at Carboxyl Residues Inside Live Cells - Ma, Nan; Hu, Jun; Zhang, Zhi-Min; Liu, Wenyan; Huang, Minhao; Fan, Youlong; Yin, Xingfeng; Wang, Jigang; Ding, Ke; Ye, Wencai; Li, Zhengqiu (Journal of the American Chemical Society, 2020)
Protein modification by chemical reagents has played an essential role in the treatment of human diseases. However, the reagents currently used are limited to the covalent modification of cysteine and lysine residues. It is thus desirable to develop novel methods that can covalently modify other residues. Despite the fact that the carboxyl residues are crucial for maintaining the protein function, few selective labeling reactions are currently available. Here, we describe a novel reactive probe, 3-phenyl-2H-azirine, that enables chemoselective modification of carboxyl groups in proteins under both in vitro and in situ conditions with excellent efficiency. Furthermore, proteome-wide profiling of reactive carboxyl residues was performed with a quantitative chemoproteomic platform.